POTENSI KETERSEDIAAN LANAN PERTANIAN DI SEPANJANG SUNGAI KAMPAR KABUPATEN PELALAWAN: (Studi Kasus: Kecamatan Langgam, Kecamatan Teluk Meranti dan Kecamatan Kuala Kampar) - Nur Febrianti; MUHAMMAD FREDESMAN Fredesman; ESI Witria (Badan Penelitian dan Pengembangan Daerah Kab. Pelalawan, 2023)
Pelalawan Regency has great potential for agricultural land because the land is still large and has not been utilized properly. The purpose of this study was to determine the extent and location of agricultural land availability in Langgam, Teluk Meranti, and Kuala Kampar sub-districts. This research used survey, descriptive, weighting, and overlay as a qualitative approach. Data used included soil type, rainfall, land morphology and slope, peat distribution, and flood risk. Data on land use rights, land cover and use, and forest cover were also required in addition to these five parameters. The results of this study show that almost all villages in Langgam Sub-district are suitable for agriculture. Langgam Village, Padang Luas Village, Pangkalan Gondai Village, Penarikan Village, Segati Village and Tambak Village have the most suitable land. In Teluk Meranti sub-district, Gambut Mutiara village, Kuala Panduk village, Labuhan Bilik village and Pangkalan Terap village have the most suitable land. In Kuala Kampar sub-district, Teluk Village, Teluk Bakau Village and Sungai Mas Village are highly suitable. The calculation of the appropriate land area for agriculture varies widely. As a result, Labuhan Bilik village, which is located in Teluk Meranti sub-district and has an area of 10.3 km2, is one of the three areas with the largest land area.